2009
DOI: 10.3354/meps07752
|View full text |Cite
|
Sign up to set email alerts
|

Differences in growth, morphology and tissue carbon and nitrogen of Macrocystis pyrifera within and at the outer edge of a giant kelp forest in California, USA

Abstract: To investigate the extent to which alteration of physical factors by giant kelp beds affects the growth of kelp within the bed, we conducted analyses of frond morphometrics at 2 mo intervals, elongation rates and tissue chemistry of individuals of Macrocystis pyrifera on the interior and edge of a kelp bed off the coast of Santa Barbara, California, USA. The density of the kelp canopy varied greatly during the 13 mo study, ranging from 0.03 to 8.03 m 2 blade tissue m -2 sea surface. Time series analysis of flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…The large influence of Macrocystis on light and flow in the Mohawk kelp forest (Gaylord et al 2007;Fram et al 2008;Stewart et al 2009) coupled with the close proximity and similar biological and physical features of the MR and MC sites (see Results) greatly reduced the chance that factors other than the presence of giant kelp would cause differences in NPP between the two sites. NPP and biomass of Macrocystis were measured monthly at a similar depth , 10 m west of the MC site as part of the Santa Barbara Coastal Long-Term Ecological Research Program's ongoing investigations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large influence of Macrocystis on light and flow in the Mohawk kelp forest (Gaylord et al 2007;Fram et al 2008;Stewart et al 2009) coupled with the close proximity and similar biological and physical features of the MR and MC sites (see Results) greatly reduced the chance that factors other than the presence of giant kelp would cause differences in NPP between the two sites. NPP and biomass of Macrocystis were measured monthly at a similar depth , 10 m west of the MC site as part of the Santa Barbara Coastal Long-Term Ecological Research Program's ongoing investigations.…”
Section: Methodsmentioning
confidence: 99%
“…However, these perspectives ignore the potential for interactions between benthic and pelagic autotrophs on intermediate scales, from hundreds of meters to kilometers, such as among reefs with and without kelp canopies, and much of the variation in coastal production can occur at this scale (Broitman and Kinlan 2006). Giant kelp, Macrocystis spp., a foundation species and ecosystem engineer, creates dense forests that provide food and physical habitat to many animal species (Foster and Schiel 1985;Graham 2004), slow water flow (Jackson and Winant 1983;Gaylord et al 2007), absorb light (Stewart et al 2009), and take up nutrients (Hurd 2000), thus shaping the entire benthic community (Dayton 1985;Clark et al 2004;Arkema et al 2009). Controlled removal experiments have shown that giant kelp suppresses the biomass of understory macroalgae (Dayton et al 1984;Reed and Foster 1984;Clark et al 2004).…”
mentioning
confidence: 99%
“…We chose data from November to match environmental conditions that affect C s , such as light availability and water temperature. The depth-averaged velocity measured in November 2006 within the Mohawk Reef kelp bed was 2.5 cm s -1 (Stewart et al 2009). Using .…”
Section: Npp Estimate For Entire Kelp Forestmentioning
confidence: 99%
“…To illustrate the simplicity and validity of the derived model, we determined the forest-averaged daily NPP for the Mohawk Reef forest off the coast of Santa Barbara, California, USA, using reported data from November 2006 , Stewart et al 2009). We chose data from November to match environmental conditions that affect C s , such as light availability and water temperature.…”
Section: Npp Estimate For Entire Kelp Forestmentioning
confidence: 99%
See 1 more Smart Citation